Temsirolimus targets multiple hallmarks of cancer to impede mesothelioma growth in vivo. Issue 8 (5th August 2015) - Vazakidou, Maria Eleni; Magkouta, Sophia; Moschos, Charalampos; Psallidas, Ioannis; Pappas, Apostolos; Psarra, Katherina; Kalomenidis, Ioannis
Abstract Background and objective The mechanistic target of rapamycin (mTOR) promotes cancer cell proliferation and survival, transduces pro‐angiogenic signals and regulates immune cell differentiation and function. We hypothesized that temsirolimus, an mTOR inhibitor, would curtail experimental mesothelioma progression in vivo by limiting tumour cell growth, abrogating tumour angiogenesis and modulating immune/inflammatory tumour milieu. Methods We produced flank and pleural syngeneic murine mesotheliomas by delivering AE17 and AB1 murine mesothelioma cells into the right flank or the pleural space of C57BL/6 and BALB/c mice, respectively. Animals were given five times/week intraperitoneal injections of 20 mg/kg temsirolimus or vehicle and were sacrificed on day 26 (flank) or on day 15 (pleural) post‐tumour cell propagation. Results Temsirolimus limited mesothelioma growth in vivo by stimulating tumour cell apoptosis, inhibiting tumour angiogenesis, enhancing tumour lymphocyte abundance and blocking pro‐tumour myeloid cell recruitment. Pleural fluid accumulation was significantly mitigated in AE17 but not in AB1 mesotheliomas. In vitro, temsirolimus hindered mesothelioma cell growth, NF‐kappaB activation and macrophage migration. Conclusions In conclusion, temsirolimus apart from inducing tumour cell apoptosis, targets tumour angiogenesis and influences inflammatory tumour microenvironment to halt experimental mesothelioma growth in vivo.